Star Wars: The Rise of Skywalker - J.J. Abrams (2026)
Star Wars; The Rise of Skywalker is a 2019 American epic space opera film produced co-written and directed by J. J. Abrams. It is the third installment of the Star Wars sequel trilogy following The Force Awakens (2015) and The Last Jedi (2017) and the ninth and final episode of the nine-part "Skywalker saga".